Pathogenetic aspects of acute upper urinary tract`s obstruction - L. Ye. Belyi (Бюллетень сибирской медицины, 2010)
In the review questions of pathogenesis of acute upper urinary tract`s obstruction are considered. The critical analysis of existing theories of upper urinary tract`s motor activity carried out. The basis mechanisms of pathogenesis — disturbs of urodynamic and pathological renovascular changes are described.